The Relationship Between Organizational Culture and Knowledge Management in Tequila Companies from Mexico - Nuñez Ramírez, Marco Alberto; Wendlandt Amezaga, Teodoro Rafael; Álvarez Medina, María Trinidad (International Journal of Advanced Corporate Learning (iJAC), 2016)
The purpose of this research is to determine the degree of association between organizational culture and knowledge management. Using a quantitative and cross-sectional design, the Pearson correlation coefficient was used to assess the relationship between variables, as well as a hierarchical multiple regression in order to measure the potential impact of organizational culture on knowledge management. To test some hypotheses, a sample of 39 tequila business organizations from the state of Jalisco was obtained, whose results provided empirical evidence that organizational culture can associate and explain to knowledge management.